2007
DOI: 10.1007/s10461-007-9253-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting HIV Transmission Risk among HIV-Infected Patients Seen in Clinical Settings

Abstract: We assessed risk of transmission among 4,016 HIV-infected patients in primary care, including men who have sex with men (MSM, n=2,109), women (n=1,104) MSM were more likely to use methamphetamines (8% versus 2% and 3% respectively), while MSW (17%) and women (12%, compared to 11% for MSM) were more likely to use cocaine. Clinical settings offer opportunities for preventing HIV transmission, particularly if interventions are tailored to sub-populations of HIV-infected patients.Predicting Transmission Risk 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 26 publications
3
82
1
1
Order By: Relevance
“…We surveyed almost 50% of the HIV-infected population in Croatia, however, and had a low refusal rate and wide inclusion criteria, which allowed us to generalize our findings to the entire HIV-infected population of about 400 persons under medical care in Croatia. Our findings were similar to behavioral data reported from recent studies in other settings (Golden et al 2007;Morin et al 2007), which showed that MSM were more likely to report risky sexual behavior than were MSW or women. Such studies have led to the development of national behavioral surveillance systems for HIV/ AIDS patients (Malitz and Eldred 2007).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We surveyed almost 50% of the HIV-infected population in Croatia, however, and had a low refusal rate and wide inclusion criteria, which allowed us to generalize our findings to the entire HIV-infected population of about 400 persons under medical care in Croatia. Our findings were similar to behavioral data reported from recent studies in other settings (Golden et al 2007;Morin et al 2007), which showed that MSM were more likely to report risky sexual behavior than were MSW or women. Such studies have led to the development of national behavioral surveillance systems for HIV/ AIDS patients (Malitz and Eldred 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Heterosexual patients of both sexes were more likely than MSM to expose their main partners to HIV and to report no casual non-concordant, unprotected sex in that period, a finding not reported in similar studies (Golden et al 2007;Morin et al 2007). There also was evidence of sero-sorting among MSW and women with casual partners.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…[23][24][25][26][27] We know there are differences in sexual risk behavior patterns between HIV-infected MSM, men who have sex with women (MSW), and women who have sex with men (WSM). [28][29][30][31][32][33] These differences suggest that the costs, benefits, and outcomes associated with serostatus disclosure may also differ between groups. 22 In fact, several studies have found differences between these three groups in serostatus disclosure to sex partners.…”
Section: Introductionmentioning
confidence: 99%